Trends in mortality from ill-defined causes among the elderly in Brazil, 1979-2013: ecological study - Martins Junior, Davi Félix; Felzemburg, Ridalva Dias Martins; Dias, Acácia Batista; Costa, Tania Maria; Santos, Pedro Nascimento Prates (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Mortality measurements are traditionally used as health indicators and are useful in describing a population’s health situation through reporting injuries that lead to death. The aim here was to analyze the temporal trend of proportional mortality from ill-defined causes (IDCs) among the elderly in Brazil from 1979 to 2013. DESIGN AND SETTING: Ecological study using data from the Mortality Information System of the Brazilian Ministry of Health. METHODS: The proportional mortality from IDCs among the elderly was calculated for each year of the study series (1979 to 2013) in Brazil, and the data were disaggregated according to sex and to the five geographical regions and states. To analyze time trends, simple linear regression coefficients were calculated. RESULTS: During the study period, there were 2,646,194 deaths from IDCs among the elderly, with a decreasing trend (ß -0.545; confidence interval, CI: -0.616 to -0.475; P < 0.000) for both males and females. This reduction was also observed in the macroregions and states, except for Amapá. The states in the northeastern region reported an average reduction of 80%. CONCLUSIONS: Mortality from IDCs among the elderly has decreased continuously since 1985, but at different rates among the different regions and states. Actions aimed at improving data records on death certificates need to be strengthened in order to continue the trend observed.